Efficient Technique for Assessing Oral Communication Skills in English for Tourism: A Case Study at Bali Tourism Polytechnic - Muliana, I Wayan; Surata, I Ketut; Lilasari, Luh Nyoman Tri (LACULTOUR: Journal of Language and Cultural Tourism, 2025)
It is generally agreed that oral communication skill is given more priority in teaching ESP for tourism compared with written one, and so is it in Poltekpar Bali (Bali Tourism Polytechnic) that educates and trains students to work or become entrepreneurs in the fields of tourism. Therefore, oral assessment becomes crucial. However, conducting this using the most common technique (i.e. one-by-one interview) takes plenty of time. This study was to find out an efficient technique for assessing oral communication skill in ESP class at Poltekpar Bali. It was an empirical classroom action research that was based on a collection of experiences and observations continuously reviewed and developed by the teachers. It was found that group oral test was an efficient technique, in which a group of students of 4 to 6 was provided with a card containing a situation relevant to their vocational subjects. They had to discuss it for about 10 minutes. Through unobtrusive listening to the discussion, the teacher carried out the assessment. This article shows how to design ‘situation cards’ and provides several examples of the cards. It also describes the procedures to be followed in handling the test, including the stages before, during, and after the implementation. Furthermore, it suggests some tips when the discussion during the test is stuck or does not work.